2011
DOI: 10.1016/j.funbio.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between intratracheal and inhalation delivery of Aspergillus fumigatus conidia in the development of fungal allergic asthma in C57BL/6 mice

Abstract: SummaryAllergic asthma is a debilitating disease of the airways characterized by airway hyperresponsiveness, eosinophilic inflammation, goblet cell metaplasia with associated mucus hypersecretion, and airway wall remodelling events, particularly subepithelial fibrosis and smooth muscle cell hyperplasia. Animal models that accurately mimic these hallmarks of allergic airways disease are critical for studying mechanisms associated with the cellular and structural changes that lead to disease pathogenesis. Asperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 36 publications
0
45
1
Order By: Relevance
“…Our previous data demonstrated that airway allergic inflammation subsides by 28 d after the second fungal inhalation and that architectural changes including fibrosis, smooth muscle cell hyperplasia, and hyaluronic acid deposition occurs in subepithelial regions of the airways (28)(29)(30). Mice in our model of CA+Flu comorbidity (with significantly fewer eosinophils) were susceptible to virus-induced morbidity marked by weight loss and lung epithelial damage, compared with AA+Flu group, which did not succumb to influenza (13).…”
Section: Eosinophils Promote Antiviral Immunity In Mice With Ca and Imentioning
confidence: 62%
“…Our previous data demonstrated that airway allergic inflammation subsides by 28 d after the second fungal inhalation and that architectural changes including fibrosis, smooth muscle cell hyperplasia, and hyaluronic acid deposition occurs in subepithelial regions of the airways (28)(29)(30). Mice in our model of CA+Flu comorbidity (with significantly fewer eosinophils) were susceptible to virus-induced morbidity marked by weight loss and lung epithelial damage, compared with AA+Flu group, which did not succumb to influenza (13).…”
Section: Eosinophils Promote Antiviral Immunity In Mice With Ca and Imentioning
confidence: 62%
“…Many of the acute and chronic features of clinical fungal asthma are recapitulated in the experimental inhalation model of allergic asthma with Aspergillus sensitization that we have developed in our laboratory [4, 7, 912]. In particular, we observe increased eosinophilia, IgE production, and a robust ECM turn over, which is exaggerated upon subsequent challenges with conidia [9, 11]. However, the relationship between ECM accumulation and inflammatory cell recruitment has not been investigated in fungal allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the intratracheal delivery may be appropriate for examination of the role played by the innate cells in the acute response to A. fumigatus, but there is an inconsistency to reproduce the chronic allergic asthma. However, inhalation challenge to mimic certain characteristic may be suited to study critical events [18]. All the same, the present methodology used in our experiments also present multiple exposures and also manifests well defined allergic disease or bronchopulmonary a common allergic human asthmatic.…”
Section: Discussionmentioning
confidence: 96%